MENINGKATKAN HASIL BELAJAR SENI TARI SISWA DENGAN MENGGUNAKAN MEDIA AUDIO VISUAL DI SMA NEGERI 1 KOTA SOLOK - Riyan Gunawan; Fuji Astuti; Susmiarti Susmiarti (SENDRATASIK UNP, 2018)
AbstractThe background of the research was low mastery of students towards a learning material that would cause the low accomplishment of the most dance learning outcomes of students. It had not reached the Minimum Completeness Criteria (KKM) in XI grade IPS.3 SMA N 1 Solok. One of the factors that influenced the low learning outcomes of students was the application of learning media that had not been able to demand the active role of students. Therefore it was necessary to do research by applying audio visual media to see student dance learning outcomes. The purposed of this study was to improve the learning outcomes of dance students in SMA N 1 Solok through the using of audio visual media. The type of this research was classroom action research. The subjects of this study were students of XI grade IPS.3 SMA N 1 Solok registered in the 2017/2018 school year consisting of 30 students. In this study, the method of data collection was using the learning outcome test in the form of posttest at the end of each cycle and observation sheet. The data obtained were analyzed using the classical learning completeness formula. Based on the results of the study, it was found that there was an enhancement of students in each cycle that obtained complete scores according to the criteria of 80. In the first cycle students were complete as many as 20 people and the incomplete were 10 people. For cycle II, the number of students who complete was 25 while 5 students who were not complete, which meant the learning outcomes of dance have been increased. Thus, it could be concluded that the application of audio visual media could improve student learning outcomes in SMA N 1 SolokKeywords: Audio Visual Media, Students’ Learning Outcomes of Dance